2017
DOI: 10.1093/ofid/ofx029
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Cytomegalovirus Reactivation and Clinical Outcomes in Immunocompetent Critically Ill Patients: A Systematic Review and Meta-Analysis

Abstract: BackgroundThe aim of our systematic review was to investigate the association between cytomegalovirus (CMV) reactivation and outcomes in immunocompetent critically ill patients.MethodsWe searched electronic databases and gray literature for original studies and abstracts published between 1990 and October 2016. The review was limited to studies including critically ill immunocompetent patients. Cytomegalovirus reactivation was defined as positive polymerase chain reaction, pp65 antigenemia, or viral culture fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 44 publications
(131 reference statements)
3
45
0
2
Order By: Relevance
“…Our study showed that universal prophylaxis outperformed the preemptive approach in CMV disease. However, CMV viremia is frequently detected in patients with severe infections, and so one must be skeptical about making a diagnosis of CMV disease in a patient with non‐specific symptoms and CMV viremia. Rigorous screening for other infectious etiologies must gain more attention to avoid the misdiagnosis of CMV disease and unnecessary exposure of recipients to highly toxic substances such as ganciclovir.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study showed that universal prophylaxis outperformed the preemptive approach in CMV disease. However, CMV viremia is frequently detected in patients with severe infections, and so one must be skeptical about making a diagnosis of CMV disease in a patient with non‐specific symptoms and CMV viremia. Rigorous screening for other infectious etiologies must gain more attention to avoid the misdiagnosis of CMV disease and unnecessary exposure of recipients to highly toxic substances such as ganciclovir.…”
Section: Discussionmentioning
confidence: 99%
“…Disorders inducing progenitor cells such as infections naturally promote the replication of CMV . The reactivation of CMV in critically ill patients is associated with adverse outcomes . However, it is unclear if CMV viremia is merely a marker of an unfavorable outcome or the cause of adverse outcomes …”
Section: Introductionmentioning
confidence: 99%
“…In particular, patients with bacterial sepsis or pneumonia have been reported to have a higher likelihood of CMV viremia ( 28 , 33 , 36 ). The risk of CMV viremia is not clearly related to disease severity at the time of admission based on prognostic and organ dysfunction scores, and the onset of CMV viremia tends to precede or accompany clinical decline ( 37 , 38 ), which support the possibility that CMV causes, rather than merely being a marker of, worse ICU outcomes in adults ( 23 25 ).…”
Section: Systemic CMV Reactivation In Immunocompetent Critically Ill mentioning
confidence: 99%
“…There have been more than 30 studies of immunologically normal, critically ill adult patients demonstrating an association between systemic CMV reactivation and worse outcomes in intensive care units (ICUs), as summarized in recent reviews ( 22 25 ). In these studies, CMV reactivation was defined as the detection of CMV in blood samples or, when feasible, in bronchoalveolar lavage (BAL) fluid, using CMV DNA PCR, antigen immunocytochemistry, or growth in shell vial culture.…”
Section: Systemic CMV Reactivation In Immunocompetent Critically Ill mentioning
confidence: 99%
See 1 more Smart Citation